Reconstruction Of The Norms Regulation Of The Clerkship At The Supreme Court From The Perspective Of A Pancasila-Based State - R. Seno Soeharjono Santoso; Agus Surono; Adnan Hamid; Zaitun Abdullah (Jurnal Ragam Pengabdian, 2026)
This study examines the reconstruction of the norms governing the clerkship system within the Supreme Court from the perspective of the Pancasila rule of law, focusing on the regulatory inconsistency concerning the appointment of clerks in appellate and first-instance courts. The issue arises from a policy shift that restricts clerk appointments to judges, creating inconsistencies with the merit system, legal certainty, and career development of judicial clerical personnel. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The findings indicate that such restrictions do not fully reflect the principles of professionalism, as they disregard the competence and experience of judicial clerical officers in case administration. Consequently, the policy limits career advancement opportunities for qualified clerical personnel and reduces the effectiveness of judicial administration. The proposed normative reconstruction emphasizes a competency-, experience-, and qualification-based career system without restricting appointments to a particular professional background. This reconstruction is expected to establish a more professional, equitable, and sustainable clerkship system consistent with the values of the Pancasila rule of law and the merit principle in judicial governance.